Corrosion-resistant high-performance steel structure material and preparation thereof

By using corrosion-resistant agents prepared by modifying miscellaneous agents and other metal elements in the steel structure, combined with crack-resistant refractory agents, the problem of wall hanging in the steel structure in the corrosion liquid is solved, and the corrosion resistance and crack-resistant refractory ability are significantly improved.

CN119501054AInactive Publication Date: 2025-02-25SHENYANG JIANZHU UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411664062.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Steel structures are prone to wall hanging when they come into contact with corrosion liquid, which increases the possibility of corrosion.

Method used

Corrosion-resistant high-performance steel structures are prepared by modified miscellaneous agents, chromium, nickel, manganese and aluminum, combined with crack-resistant refractory agents prepared by short mullite fibers, coal gangue powder and short zirconia refractory fibers, and corrosion-resistant high-performance steel structures are prepared through arc furnace casting, forging, quenching and deep-cold treatment.

Benefits of technology

It effectively improves the smoothness of the steel structure surface, reduces the wall hanging ability of corrosive solutions, extends the corrosion resistance of the steel structure, and improves the crack and fire resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005144171760000131
    Figure BDA0005144171760000131
Patent Text Reader

Abstract

The invention relates to a corrosion-resistant high-performance steel structure material and preparation thereof, and belongs to the technical field of steel structures, and the corrosion-resistant high-performance steel structure material is prepared from the following raw materials in parts by weight: 1-3 parts of carbon, 64-77 parts of iron, 3-6 parts of a corrosion-resistant agent and 2-5 parts of an anti-cracking fire-resistant agent; wherein the corrosion-resistant agent is prepared from the following components in parts by weight: 0.4 to 1.2 parts of an impurity modifying agent, 1 to 1.3 parts of chromium, 1.2 to 1.7 parts of nickel, 0.3 to 0.8 part of manganese and 2 to 4 parts of aluminum. The impurity modifying agent is matched with the corrosion-resistant agent prepared from chromium, nickel, manganese and aluminum, so that the smoothness of the surface of the corrosion-resistant high-performance steel structure is effectively improved, the wall hanging capacity of a corrosive solution is reduced as much as possible, the contact time of the corrosive solution and the surface of the corrosion-resistant high-performance steel structure is shortened, and the corrosion resistance of the corrosion-resistant high-performance steel structure is improved; according to the anti-crack fire-resistant agent prepared from the short mullite fibers, the coal gangue powder and the short zirconium oxide fire-resistant fibers, the crack length, the crack depth, the crack width and the crack number are effectively reduced, and therefore the anti-crack fire-resistant capacity of the corrosion-resistant high-performance steel structure is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of steel structures, and in particular relates to a corrosion-resistant high-performance steel structure material and a preparation method thereof. Background Art

[0002] Steel structure is an engineering structure composed of steel beams, steel columns, steel trusses and other components made of steel and steel plates. It has the advantages of light weight, simple construction and strong load-bearing capacity. It is widely used in large factories, venues, super high-rise buildings, bridges, residential buildings, municipal and agricultural buildings, aerospace, marine engineering, rail transportation, sports facilities, exhibition halls, amusement facilities and other fields;

[0003] After the steel structure is put into use, it is easy to come into contact with common corrosive liquids in daily life, such as acidic corrosives, alkaline corrosives, hydrogen peroxide, formaldehyde solution and sodium hypochlorite solution. Although the surface of the steel structure is relatively smooth, when the surface of the steel structure comes into contact with the above-mentioned corrosive liquids, wall hanging will still occur, thereby increasing the possibility of corrosion of the steel structure. Summary of the invention

[0004] The purpose of the present invention is to provide a corrosion-resistant high-performance steel structure material and its preparation in order to solve the above-mentioned problems.

[0005] The present invention achieves the above-mentioned purpose through the following technical solutions:

[0006] The present invention provides a corrosion-resistant high-performance steel structure material, wherein the raw materials for its preparation include, by weight: 1-3 parts of carbon, 64-77 parts of iron, 3-6 parts of corrosion-resistant agent, and 2-5 parts of anti-cracking fire-resistant agent;

[0007] Wherein, by weight, the corrosion resistance agent includes 0.4-1.2 parts of impurity modifier, 1-1.3 parts of chromium, 1.2-1.7 parts of nickel, 0.3-0.8 parts of manganese, and 2-4 parts of aluminum.

[0008] As a further optimization scheme of the present invention, the preparation process of the impurity-modifying agent is as follows:

[0009] (i) Mixing rare earth cerium powder, rare earth praseodymium powder and rare earth scandium powder, controlling the time to be 20-30 minutes, controlling the rotation speed to be 10-13r / min, and obtaining a mixed powder; (ii) Pour the mixed powder into a melting furnace for melting, controlling the temperature to be 2200-2300°C, and controlling the time to be 30-50 minutes, and obtaining a mixed liquid; (iii) Cooling the mixed liquid into a mold to obtain a rare earth block; (iv) Grinding the rare earth block into powder, controlling the powder particle diameter to be 0.001-0.003um, and obtaining rare earth mixed microparticles.

[0010] As a further optimization scheme of the present invention, the mass ratio of the rare earth cerium powder, the rare earth praseodymium powder and the rare earth scandium powder is 1:0.2:0.4.

[0011] As a further optimization scheme of the present invention, the preparation process of the anti-cracking refractory agent is:

[0012] (i) Mix short mullite fiber, coal gangue powder and short zirconia refractory fiber, control the time to be 20-30min, control the rotation speed to be 10-13r / min, and obtain a mixture; (ii) Spread the mixture on a filter screen, and then spray it with a vulcanizing agent, control the spraying time to be 4-6h, and obtain a vulcanized material; (iii) Rinse the vulcanized material with water, control the rinsing time to be 2-4h, and then dry it to obtain a crack-resistant refractory agent.

[0013] As a further optimization scheme of the present invention, the preparation process of the short mullite fiber is: using a fiber crusher to prepare the mullite fiber into short mullite fiber with a length of 1-2 mm and a diameter of 0.1-0.2 um;

[0014] The preparation process of the short zirconia refractory fiber is as follows: using a fiber crusher to prepare the zirconia refractory fiber into short zirconia refractory fiber with a length of 1-2 mm and a diameter of 0.1-0.2 um.

[0015] As a further optimization scheme of the present invention, the mass ratio of the short mullite fiber, the coal gangue powder and the short zirconia refractory fiber is 1:1.2:1.3.

[0016] The method for preparing the above-mentioned corrosion-resistant high-performance steel structural material is characterized by comprising the following steps:

[0017] S1, corrosion resistant agent: mix and stir the impurity modifying agent, chromium, nickel, manganese and aluminum, control the stirring time to 20-30min, and control the stirring speed to 10-13r / min;

[0018] S2, adding carbon, iron, corrosion resistant agent and anti-cracking refractory agent into an electric arc furnace to obtain molten steel;

[0019] S3, casting molten steel to form an electrode rod, and isothermally annealing the electrode rod to obtain an ingot;

[0020] S4, electroslag remelting the ingot to obtain an electroslag ingot;

[0021] S5, forging the electroslag ingot using a forging machine, and controlling the forging time to be 10-20 minutes;

[0022] S6, quenching and heat-insulating the electroslag ingot in S5, tempering, and controlling the heat treatment temperature to be 1170°C-1200°C for quenching and 545°C-555°C for tempering;

[0023] S7. Cryogenically treat the electroslag ingot in S6, control the cryogenic temperature to -163-190°C, and keep it warm for 36-43 hours to obtain a corrosion-resistant high-performance steel structure.

[0024] The beneficial effects of the present invention are as follows: the corrosion-resistant agent prepared by mixing impurities, chromium, nickel, manganese and aluminum effectively improves the smoothness of the surface of the corrosion-resistant high-performance steel structure, minimizes the wall-hanging ability of the corrosive solution, and reduces the contact time between the corrosive solution and the surface of the corrosion-resistant high-performance steel structure, thereby improving the corrosion resistance of the corrosion-resistant high-performance steel structure; the anti-cracking refractory agent prepared by short mullite fiber, coal gangue powder and short zirconia refractory fiber effectively reduces the crack length, crack depth, crack width and crack number, thereby improving the anti-cracking and fire-resistant ability of the corrosion-resistant high-performance steel structure. DETAILED DESCRIPTION

[0025] The present application is described in further detail below. It is necessary to point out that the following specific implementation methods are only used to further illustrate the present application and cannot be understood as limiting the scope of protection of the present application. Technicians in this field can make some non-essential improvements and adjustments to the present application based on the above application content.

[0026] 1. Materials

[0027] Unless otherwise specified, the methods used in the present invention are conventional methods known to those skilled in the art, and the reagents and other materials used are commercially available products unless otherwise specified.

[0028] The water in the present invention is pure water; the vulcanizing agent adopts XG-818 platinum vulcanizing agent under the Haocheng brand.

[0029] 2. Embodiment

[0030] Example 1

[0031] A corrosion-resistant high-performance steel structure material, wherein the raw materials for its preparation include, by weight: 1 part of carbon, 64 parts of iron, 3 parts of corrosion-resistant agent, and 2 parts of anti-cracking fire-resistant agent;

[0032] Wherein, the corrosion resistant agent includes 0.4 parts of impurity modifier, 1 parts of chromium, 1.2 parts of nickel, 0.3 parts of manganese and 2 parts of aluminum by weight;

[0033] The method for preparing the above-mentioned corrosion-resistant high-performance steel structural material is characterized by comprising the following steps:

[0034] Modification of impurities: (i) Mixing rare earth cerium powder, rare earth praseodymium powder and rare earth scandium powder (the mass ratio of rare earth cerium powder, rare earth praseodymium powder and rare earth scandium powder is 1:0.2:0.4), controlling the time to be 20 minutes, controlling the speed to be 10r / min, and obtaining a mixed powder; (ii) Pour the mixed powder into a melting furnace for melting, controlling the temperature to be 2200°C, controlling the time to be 30 minutes, and obtaining a mixed liquid; (iii) Cooling and molding the mixed liquid to obtain a rare earth block; (iv) Grinding the rare earth block into powder, controlling the diameter of the powder particles to be 0.001um, and obtaining rare earth mixed particles;

[0035] The preparation process of short mullite fiber is as follows: using a fiber crusher to prepare the mullite fiber into short mullite fiber with a length of 1 mm and a diameter of 0.1 um;

[0036] The preparation process of the short zirconia refractory fiber is as follows: the zirconia refractory fiber is prepared into a short zirconia refractory fiber with a length of 1 mm and a diameter of 0.1 um by using a fiber crusher;

[0037] Anti-cracking refractory agent: (i) short mullite fiber, coal gangue powder and short zirconia refractory fiber (the mass ratio of short mullite fiber, coal gangue powder and short zirconia refractory fiber is 1:1.2:1.3) are mixed, the control time is 20 minutes, the control speed is 10r / min, and a mixture is obtained; (ii) the mixture is spread on a filter screen, and then sprayed with a vulcanizing agent, the spraying time is controlled to be 4 hours, and a vulcanized material is obtained; (iii) the vulcanized material is rinsed with water, the rinsing time is controlled to be 2 hours, and then dried to obtain an anti-cracking refractory agent;

[0038] Corrosion resistant agent: Mix and stir the impurity modifying agent, chromium, nickel, manganese and aluminum, control the stirring time to 20 minutes, and control the stirring speed to 10r / min;

[0039] Adding carbon, iron, corrosion resistant agent and anti-cracking refractory agent into an electric arc furnace to obtain molten steel;

[0040] Casting molten steel to form an electrode rod, and isothermally annealing the electrode rod to obtain an ingot;

[0041] The ingot is subjected to electroslag remelting to obtain an electroslag ingot;

[0042] The electroslag ingot is forged using a forging machine, and the forging time is controlled to be 10 minutes;

[0043] The electroslag ingot is quenched and kept warm, and then tempered. The heat treatment temperature is controlled to be 1170°C for quenching and 545°C for tempering.

[0044] The electroslag ingots are cryogenically treated, the cryogenic temperature is controlled at -163°C, and the temperature is kept for 36 hours to obtain a corrosion-resistant high-performance steel structure.

[0045] Example 2

[0046] A corrosion-resistant high-performance steel structure material, wherein the raw materials for its preparation include, by weight: 2 parts of carbon, 70.5 parts of iron, 4.5 parts of corrosion-resistant agent, and 3.5 parts of anti-cracking fire-resistant agent;

[0047] Wherein, the corrosion resistant agent includes 0.8 parts of impurity modifier, 1.15 parts of chromium, 1.45 parts of nickel, 0.55 parts of manganese and 3 parts of aluminum by weight;

[0048] The method for preparing the above-mentioned corrosion-resistant high-performance steel structural material is characterized by comprising the following steps:

[0049] Modification of impurities: (i) Mixing rare earth cerium powder, rare earth praseodymium powder and rare earth scandium powder (the mass ratio of rare earth cerium powder, rare earth praseodymium powder and rare earth scandium powder is 1:0.2:0.4), controlling the time to be 25 minutes, controlling the speed to be 11.5r / min, and obtaining a mixed powder; (ii) Pour the mixed powder into a melting furnace for melting, controlling the temperature to be 2250°C, controlling the time to be 40 minutes, and obtaining a mixed liquid; (iii) Cooling and molding the mixed liquid to obtain a rare earth block; (iv) Grinding the rare earth block into powder, controlling the powder particle diameter to be 0.002um, and obtaining rare earth mixed particles;

[0050] The preparation process of short mullite fiber is as follows: using a fiber crusher to prepare the mullite fiber into short mullite fiber with a length of 1.5 mm and a diameter of 0.15 um;

[0051] The preparation process of the short zirconia refractory fiber is as follows: the zirconia refractory fiber is prepared into a short zirconia refractory fiber with a length of 1.5 mm and a diameter of 0.15 um by using a fiber crusher;

[0052] Anti-cracking refractory agent: (i) short mullite fiber, coal gangue powder and short zirconia refractory fiber (the mass ratio of short mullite fiber, coal gangue powder and short zirconia refractory fiber is 1:1.2:1.3) are mixed, the control time is 25 minutes, the control speed is 11.5r / min, and a mixture is obtained; (ii) the mixture is spread on a filter screen, and then sprayed with a vulcanizing agent, the spraying time is controlled to be 5 hours, and a vulcanized material is obtained; (iii) the vulcanized material is rinsed with water, the rinsing time is controlled to be 3 hours, and then dried to obtain an anti-cracking refractory agent;

[0053] Corrosion resistant agent: Mix and stir the impurity modifying agent, chromium, nickel, manganese and aluminum, control the stirring time to 25 minutes, and control the stirring speed to 11.5r / min;

[0054] Adding carbon, iron, corrosion resistant agent and anti-cracking refractory agent into an electric arc furnace to obtain molten steel;

[0055] Casting molten steel to form an electrode rod, and isothermally annealing the electrode rod to obtain an ingot;

[0056] The ingot is subjected to electroslag remelting to obtain an electroslag ingot;

[0057] The electroslag ingot is forged using a forging machine, and the forging time is controlled to be 15 minutes;

[0058] The electroslag ingot is quenched and kept warm, and then tempered. The heat treatment temperature is controlled to be 1185°C for quenching and 550°C for tempering.

[0059] The electroslag ingots are cryogenically treated, the cryogenic temperature is controlled at -176.5°C, and the temperature is kept for 39.5 hours to obtain a corrosion-resistant high-performance steel structure.

[0060] Example 3

[0061] A corrosion-resistant high-performance steel structure material, wherein the raw materials for its preparation include, by weight: 3 parts of carbon, 77 parts of iron, 6 parts of corrosion-resistant agent, and 5 parts of anti-cracking fire-resistant agent;

[0062] Wherein, the corrosion resistant agent includes 1.2 parts of impurity modifier, 1.3 parts of chromium, 1.7 parts of nickel, 0.8 parts of manganese and 4 parts of aluminum by weight;

[0063] The method for preparing the above-mentioned corrosion-resistant high-performance steel structural material is characterized by comprising the following steps:

[0064] Modification of impurities: (i) Mixing rare earth cerium powder, rare earth praseodymium powder and rare earth scandium powder (the mass ratio of rare earth cerium powder, rare earth praseodymium powder and rare earth scandium powder is 1:0.2:0.4), controlling the time to be 30 minutes, controlling the speed to be 13r / min, and obtaining a mixed powder; (ii) Pour the mixed powder into a melting furnace for melting, controlling the temperature to be 2300°C, controlling the time to be 50 minutes, and obtaining a mixed liquid; (iii) Cooling and molding the mixed liquid to obtain a rare earth block; (iv) Grinding the rare earth block into powder, controlling the powder particle diameter to be 0.003um, and obtaining rare earth mixed particles;

[0065] The preparation process of short mullite fiber is as follows: using a fiber crusher to prepare the mullite fiber into short mullite fiber with a length of 2 mm and a diameter of 0.2 um;

[0066] The preparation process of the short zirconia refractory fiber is as follows: the zirconia refractory fiber is prepared into a short zirconia refractory fiber with a length of 2 mm and a diameter of 0.2 um by using a fiber crusher;

[0067] Anti-cracking refractory agent: (i) short mullite fiber, coal gangue powder and short zirconia refractory fiber (the mass ratio of short mullite fiber, coal gangue powder and short zirconia refractory fiber is 1:1.2:1.3) are mixed, the control time is 30 minutes, the control speed is 13r / min, and a mixture is obtained; (ii) the mixture is spread on a filter screen, and then sprayed with a vulcanizing agent, the spraying time is controlled to be 6 hours, and a vulcanized material is obtained; (iii) the vulcanized material is rinsed with water, the rinsing time is controlled to be 4 hours, and then dried to obtain an anti-cracking refractory agent;

[0068] Corrosion resistant agent: Mix and stir the impurity modifying agent, chromium, nickel, manganese and aluminum, control the stirring time to 30 minutes, and control the stirring speed to 13r / min;

[0069] Adding carbon, iron, corrosion resistant agent and anti-cracking refractory agent into an electric arc furnace to obtain molten steel;

[0070] Casting molten steel to form an electrode rod, and isothermally annealing the electrode rod to obtain an ingot;

[0071] The ingot is subjected to electroslag remelting to obtain an electroslag ingot;

[0072] The electroslag ingot is forged using a forging machine, and the forging time is controlled to be 20 minutes;

[0073] The electroslag ingot is quenched and kept warm, and then tempered. The heat treatment temperature is controlled to be 1200°C for quenching and 555°C for tempering.

[0074] The electroslag ingots are cryogenically treated, the cryogenic temperature is controlled at -190°C, and the temperature is kept at -190°C for 43 hours to obtain a corrosion-resistant high-performance steel structure.

[0075] Comparative Example 1

[0076] A corrosion-resistant high-performance steel structure material, wherein the raw materials for its preparation include, by weight: 2 parts of carbon, 70.5 parts of iron, 4.5 parts of corrosion-resistant agent, and 3.5 parts of anti-cracking fire-resistant agent;

[0077] Wherein, the corrosion-resistant agent includes 1.3 parts of chromium, 1.65 parts of nickel, 0.63 parts of manganese, and 3.37 parts of aluminum by weight;

[0078] The method for preparing the above-mentioned corrosion-resistant high-performance steel structural material is characterized by comprising the following steps:

[0079] Modification of impurities: (i) Mixing rare earth cerium powder, rare earth praseodymium powder and rare earth scandium powder (the mass ratio of rare earth cerium powder, rare earth praseodymium powder and rare earth scandium powder is 1:0.2:0.4), controlling the time to be 25 minutes, controlling the speed to be 11.5r / min, and obtaining a mixed powder; (ii) Pour the mixed powder into a melting furnace for melting, controlling the temperature to be 2250°C, controlling the time to be 40 minutes, and obtaining a mixed liquid; (iii) Cooling and molding the mixed liquid to obtain a rare earth block; (iv) Grinding the rare earth block into powder, controlling the powder particle diameter to be 0.002um, and obtaining rare earth mixed particles;

[0080] The preparation process of short mullite fiber is as follows: using a fiber crusher to prepare the mullite fiber into short mullite fiber with a length of 1.5 mm and a diameter of 0.15 um;

[0081] The preparation process of the short zirconia refractory fiber is as follows: the zirconia refractory fiber is prepared into a short zirconia refractory fiber with a length of 1.5 mm and a diameter of 0.15 um by using a fiber crusher;

[0082] Anti-cracking refractory agent: (i) short mullite fiber, coal gangue powder and short zirconia refractory fiber (the mass ratio of short mullite fiber, coal gangue powder and short zirconia refractory fiber is 1:1.2:1.3) are mixed, the control time is 25 minutes, the control speed is 11.5r / min, and a mixture is obtained; (ii) the mixture is spread on a filter screen, and then sprayed with a vulcanizing agent, the spraying time is controlled to be 5 hours, and a vulcanized material is obtained; (iii) the vulcanized material is rinsed with water, the rinsing time is controlled to be 3 hours, and then dried to obtain an anti-cracking refractory agent;

[0083] Corrosion resistant agent: Mix and stir the impurity modifying agent, chromium, nickel, manganese and aluminum, control the stirring time to 25 minutes, and control the stirring speed to 11.5r / min;

[0084] Adding carbon, iron, corrosion resistant agent and anti-cracking refractory agent into an electric arc furnace to obtain molten steel;

[0085] Casting molten steel to form an electrode rod, and isothermally annealing the electrode rod to obtain an ingot;

[0086] The ingot is subjected to electroslag remelting to obtain an electroslag ingot;

[0087] The electroslag ingot is forged using a forging machine, and the forging time is controlled to be 15 minutes;

[0088] The electroslag ingot is quenched and kept warm, and then tempered. The heat treatment temperature is controlled to be 1185°C for quenching and 550°C for tempering.

[0089] The electroslag ingots are cryogenically treated, the cryogenic temperature is controlled at -176.5°C, and the temperature is kept for 39.5 hours to obtain a corrosion-resistant high-performance steel structure.

[0090] Comparative Example 2

[0091] A corrosion-resistant high-performance steel structure material, wherein the raw materials for its preparation include, by weight: 2 parts of carbon, 70.5 parts of iron, 4.5 parts of corrosion-resistant agent, and 3.5 parts of anti-cracking fire-resistant agent;

[0092] Wherein, the corrosion resistant agent is specifically a modification agent, measured by weight;

[0093] The method for preparing the above-mentioned corrosion-resistant high-performance steel structural material is characterized by comprising the following steps:

[0094] Modification of impurities: (i) Mixing rare earth cerium powder, rare earth praseodymium powder and rare earth scandium powder (the mass ratio of rare earth cerium powder, rare earth praseodymium powder and rare earth scandium powder is 1:0.2:0.4), controlling the time to be 25 minutes, controlling the speed to be 11.5r / min, and obtaining a mixed powder; (ii) Pour the mixed powder into a melting furnace for melting, controlling the temperature to be 2250°C, controlling the time to be 40 minutes, and obtaining a mixed liquid; (iii) Cooling and molding the mixed liquid to obtain a rare earth block; (iv) Grinding the rare earth block into powder, controlling the powder particle diameter to be 0.002um, and obtaining rare earth mixed particles;

[0095] The preparation process of short mullite fiber is as follows: using a fiber crusher to prepare the mullite fiber into short mullite fiber with a length of 1.5 mm and a diameter of 0.15 um;

[0096] The preparation process of the short zirconia refractory fiber is as follows: the zirconia refractory fiber is prepared into a short zirconia refractory fiber with a length of 1.5 mm and a diameter of 0.15 um by using a fiber crusher;

[0097] Anti-cracking refractory agent: (i) short mullite fiber, coal gangue powder and short zirconia refractory fiber (the mass ratio of short mullite fiber, coal gangue powder and short zirconia refractory fiber is 1:1.2:1.3) are mixed, the control time is 25 minutes, the control speed is 11.5r / min, and a mixture is obtained; (ii) the mixture is spread on a filter screen, and then sprayed with a vulcanizing agent, the spraying time is controlled to be 5 hours, and a vulcanized material is obtained; (iii) the vulcanized material is rinsed with water, the rinsing time is controlled to be 3 hours, and then dried to obtain an anti-cracking refractory agent;

[0098] Corrosion resistant agent: Mix and stir the impurity modifying agent, chromium, nickel, manganese and aluminum, control the stirring time to 25 minutes, and control the stirring speed to 11.5r / min;

[0099] Adding carbon, iron, corrosion resistant agent and anti-cracking refractory agent into an electric arc furnace to obtain molten steel;

[0100] Casting molten steel to form an electrode rod, and isothermally annealing the electrode rod to obtain an ingot;

[0101] The ingot is subjected to electroslag remelting to obtain an electroslag ingot;

[0102] The electroslag ingot is forged using a forging machine, and the forging time is controlled to be 15 minutes;

[0103] The electroslag ingot is quenched and kept warm, and then tempered. The heat treatment temperature is controlled to be 1185°C for quenching and 550°C for tempering.

[0104] The electroslag ingots are cryogenically treated, the cryogenic temperature is controlled at -176.5°C, and the temperature is kept for 39.5 hours to obtain a corrosion-resistant high-performance steel structure.

[0105] Comparative Example 3

[0106] A corrosion-resistant high-performance steel structural material, wherein the raw materials for its preparation include, by weight: 2.02 parts of carbon, 73.7 parts of iron, and 4.78 parts of corrosion-resistant agent;

[0107] Wherein, the corrosion resistant agent includes 0.8 parts of impurity modifier, 1.15 parts of chromium, 1.45 parts of nickel, 0.55 parts of manganese and 3 parts of aluminum by weight;

[0108] The method for preparing the above-mentioned corrosion-resistant high-performance steel structural material is characterized by comprising the following steps:

[0109] Modification of impurities: (i) Mixing rare earth cerium powder, rare earth praseodymium powder and rare earth scandium powder (the mass ratio of rare earth cerium powder, rare earth praseodymium powder and rare earth scandium powder is 1:0.2:0.4), controlling the time to be 25 minutes, controlling the speed to be 11.5r / min, and obtaining a mixed powder; (ii) Pour the mixed powder into a melting furnace for melting, controlling the temperature to be 2250°C, controlling the time to be 40 minutes, and obtaining a mixed liquid; (iii) Cooling and molding the mixed liquid to obtain a rare earth block; (iv) Grinding the rare earth block into powder, controlling the powder particle diameter to be 0.002um, and obtaining rare earth mixed particles;

[0110] Corrosion resistant agent: Mix and stir the impurity modifying agent, chromium, nickel, manganese and aluminum, control the stirring time to 25 minutes, and control the stirring speed to 11.5r / min;

[0111] Add carbon, iron and corrosion resistant agent into an electric arc furnace to obtain molten steel;

[0112] Casting molten steel to form an electrode rod, and isothermally annealing the electrode rod to obtain an ingot;

[0113] The ingot is subjected to electroslag remelting to obtain an electroslag ingot;

[0114] The electroslag ingot is forged using a forging machine, and the forging time is controlled to be 15 minutes;

[0115] The electroslag ingot is quenched and kept warm, and then tempered. The heat treatment temperature is controlled to be 1185°C for quenching and 550°C for tempering.

[0116] The electroslag ingots are cryogenically treated, the cryogenic temperature is controlled at -176.5°C, and the temperature is kept for 39.5 hours to obtain a corrosion-resistant high-performance steel structure.

[0117] Comparative Example 4

[0118] A corrosion-resistant high-performance steel structure material, wherein the raw materials for its preparation include, by weight: 2 parts of carbon, 70.5 parts of iron, 4.5 parts of corrosion-resistant agent, and 3.5 parts of anti-cracking fire-resistant agent;

[0119] Wherein, the corrosion resistant agent includes 0.8 parts of impurity modifier, 1.15 parts of chromium, 1.45 parts of nickel, 0.55 parts of manganese and 3 parts of aluminum by weight;

[0120] The method for preparing the above-mentioned corrosion-resistant high-performance steel structural material is characterized by comprising the following steps:

[0121] Modification of impurities: (i) Mixing rare earth cerium powder, rare earth praseodymium powder and rare earth scandium powder (the mass ratio of rare earth cerium powder, rare earth praseodymium powder and rare earth scandium powder is 1:0.2:0.4), controlling the time to be 25 minutes, controlling the speed to be 11.5r / min, and obtaining a mixed powder; (ii) Pour the mixed powder into a melting furnace for melting, controlling the temperature to be 2250°C, controlling the time to be 40 minutes, and obtaining a mixed liquid; (iii) Cooling and molding the mixed liquid to obtain a rare earth block; (iv) Grinding the rare earth block into powder, controlling the powder particle diameter to be 0.002um, and obtaining rare earth mixed particles;

[0122] The preparation process of the short zirconia refractory fiber is as follows: the zirconia refractory fiber is prepared into a short zirconia refractory fiber with a length of 1.5 mm and a diameter of 0.15 um by using a fiber crusher;

[0123] Anti-cracking refractory agent: (i) Mixing coal gangue powder and short zirconia refractory fiber (the mass ratio of coal gangue powder to short zirconia refractory fiber is 1.68:1.82), controlling the time to be 25 minutes, controlling the speed to be 11.5r / min, and obtaining a mixture; (ii) Spreading the mixture on a filter screen, and then spraying it with a vulcanizing agent, controlling the spraying time to be 5 hours, and obtaining a vulcanized material; (iii) Rinse the vulcanized material with water, controlling the rinsing time to be 3 hours, and then drying it to obtain an anti-cracking refractory agent;

[0124] Corrosion resistant agent: Mix and stir the impurity modifying agent, chromium, nickel, manganese and aluminum, control the stirring time to 25 minutes, and control the stirring speed to 11.5r / min;

[0125] Adding carbon, iron, corrosion resistant agent and anti-cracking refractory agent into an electric arc furnace to obtain molten steel;

[0126] Casting molten steel to form an electrode rod, and isothermally annealing the electrode rod to obtain an ingot;

[0127] The ingot is subjected to electroslag remelting to obtain an electroslag ingot;

[0128] The electroslag ingot is forged using a forging machine, and the forging time is controlled to be 15 minutes;

[0129] The electroslag ingot is quenched and kept warm, and then tempered. The heat treatment temperature is controlled to be 1185°C for quenching and 550°C for tempering.

[0130] The electroslag ingots are cryogenically treated, the cryogenic temperature is controlled at -176.5°C, and the temperature is kept for 39.5 hours to obtain a corrosion-resistant high-performance steel structure.

[0131] Comparative Example 5

[0132] A corrosion-resistant high-performance steel structure material, wherein the raw materials for its preparation include, by weight: 2 parts of carbon, 70.5 parts of iron, 4.5 parts of corrosion-resistant agent, and 3.5 parts of anti-cracking fire-resistant agent;

[0133] Wherein, the corrosion resistant agent includes 0.8 parts of impurity modifier, 1.15 parts of chromium, 1.45 parts of nickel, 0.55 parts of manganese and 3 parts of aluminum by weight;

[0134] The method for preparing the above-mentioned corrosion-resistant high-performance steel structural material is characterized by comprising the following steps:

[0135] Modification of impurities: (i) Mixing rare earth cerium powder, rare earth praseodymium powder and rare earth scandium powder (the mass ratio of rare earth cerium powder, rare earth praseodymium powder and rare earth scandium powder is 1:0.2:0.4), controlling the time to be 25 minutes, controlling the speed to be 11.5r / min, and obtaining a mixed powder; (ii) Pour the mixed powder into a melting furnace for melting, controlling the temperature to be 2250°C, controlling the time to be 40 minutes, and obtaining a mixed liquid; (iii) Cooling and molding the mixed liquid to obtain a rare earth block; (iv) Grinding the rare earth block into powder, controlling the powder particle diameter to be 0.002um, and obtaining rare earth mixed particles;

[0136] The preparation process of short mullite fiber is as follows: using a fiber crusher to prepare the mullite fiber into short mullite fiber with a length of 1.5 mm and a diameter of 0.15 um;

[0137] The preparation process of the short zirconia refractory fiber is as follows: the zirconia refractory fiber is prepared into a short zirconia refractory fiber with a length of 1.5 mm and a diameter of 0.15 um by using a fiber crusher;

[0138] Anti-cracking refractory agent: (i) short mullite fiber and short zirconia refractory fiber (the mass ratio of short mullite fiber to short zirconia refractory fiber is 1.52:1.98) are mixed, the control time is 25 minutes, the control speed is 11.5r / min, and a mixture is obtained; (ii) the mixture is spread on a filter screen, and then sprayed with a vulcanizing agent, the spraying time is controlled to be 5 hours, and a vulcanized material is obtained; (iii) the vulcanized material is rinsed with water, the rinsing time is controlled to be 3 hours, and then dried to obtain an anti-cracking refractory agent;

[0139] Corrosion resistant agent: Mix and stir the impurity modifying agent, chromium, nickel, manganese and aluminum, control the stirring time to 25 minutes, and control the stirring speed to 11.5r / min;

[0140] Adding carbon, iron, corrosion resistant agent and anti-cracking refractory agent into an electric arc furnace to obtain molten steel;

[0141] Casting molten steel to form an electrode rod, and isothermally annealing the electrode rod to obtain an ingot;

[0142] The ingot is subjected to electroslag remelting to obtain an electroslag ingot;

[0143] The electroslag ingot is forged using a forging machine, and the forging time is controlled to be 15 minutes;

[0144] The electroslag ingot is quenched and kept warm, and then tempered. The heat treatment temperature is controlled to be 1185°C for quenching and 550°C for tempering.

[0145] The electroslag ingots are cryogenically treated, the cryogenic temperature is controlled at -176.5°C, and the temperature is kept for 39.5 hours to obtain a corrosion-resistant high-performance steel structure.

[0146] Comparative Example 6

[0147] A corrosion-resistant high-performance steel structure material, wherein the raw materials for its preparation include, by weight: 2 parts of carbon, 70.5 parts of iron, 4.5 parts of corrosion-resistant agent, and 3.5 parts of anti-cracking fire-resistant agent;

[0148] Wherein, the corrosion resistant agent includes 0.8 parts of impurity modifier, 1.15 parts of chromium, 1.45 parts of nickel, 0.55 parts of manganese and 3 parts of aluminum by weight;

[0149] The method for preparing the above-mentioned corrosion-resistant high-performance steel structural material is characterized by comprising the following steps:

[0150] Modification of impurities: (i) Mixing rare earth cerium powder, rare earth praseodymium powder and rare earth scandium powder (the mass ratio of rare earth cerium powder, rare earth praseodymium powder and rare earth scandium powder is 1:0.2:0.4), controlling the time to be 25 minutes, controlling the speed to be 11.5r / min, and obtaining a mixed powder; (ii) Pour the mixed powder into a melting furnace for melting, controlling the temperature to be 2250°C, controlling the time to be 40 minutes, and obtaining a mixed liquid; (iii) Cooling and molding the mixed liquid to obtain a rare earth block; (iv) Grinding the rare earth block into powder, controlling the powder particle diameter to be 0.002um, and obtaining rare earth mixed particles;

[0151] The preparation process of short mullite fiber is as follows: using a fiber crusher to prepare the mullite fiber into short mullite fiber with a length of 1.5 mm and a diameter of 0.15 um;

[0152] Anti-cracking refractory agent: (i) short mullite fiber and coal gangue powder (the mass ratio of short mullite fiber to coal gangue powder is 1.6:1.9) are mixed, the control time is 25 minutes, the control speed is 11.5r / min, and a mixture is obtained; (ii) the mixture is spread on a filter screen, and then sprayed with a vulcanizing agent, the spraying time is controlled to be 5 hours, and a vulcanized material is obtained; (iii) the vulcanized material is rinsed with water, the rinsing time is controlled to be 3 hours, and then dried to obtain an anti-cracking refractory agent;

[0153] Corrosion resistant agent: Mix and stir the impurity modifying agent, chromium, nickel, manganese and aluminum, control the stirring time to 25 minutes, and control the stirring speed to 11.5r / min;

[0154] Adding carbon, iron, corrosion resistant agent and anti-cracking refractory agent into an electric arc furnace to obtain molten steel;

[0155] Casting molten steel to form an electrode rod, and isothermally annealing the electrode rod to obtain an ingot;

[0156] The ingot is subjected to electroslag remelting to obtain an electroslag ingot;

[0157] The electroslag ingot is forged using a forging machine, and the forging time is controlled to be 15 minutes;

[0158] The electroslag ingot is quenched and kept warm, and then tempered. The heat treatment temperature is controlled to be 1185°C for quenching and 550°C for tempering.

[0159] The electroslag ingots are cryogenically treated, the cryogenic temperature is controlled at -176.5°C, and the temperature is kept for 39.5 hours to obtain a corrosion-resistant high-performance steel structure.

[0160] III. Methods

[0161] 3.1 Wall hanging test experiment

[0162] 1) Experimental Materials

[0163] Vinegar essence 250ml

[0164] Sodium hydroxide solution 250ml

[0165] Hydrogen peroxide 250ml

[0166] Formaldehyde solution 250ml

[0167] Sodium hypochlorite solution 250ml

[0168] 2) Experimental procedures

[0169] ① Five pieces of corrosion-resistant high-performance steel structures prepared by Examples 1-3 and Comparative Examples 1-2, each piece is 2m long*2m wide*1cm thick;

[0170] ② Place each piece of corrosion-resistant high-performance steel structure at 60 degrees;

[0171] ③ Pour 10ml of different solutions (one of acetic acid, sodium hydroxide solution, hydrogen peroxide, formaldehyde solution, sodium hypochlorite solution) on the length and width of each piece of corrosion-resistant high-performance steel structure at the same height;

[0172] ④ After 3 minutes, observe the wall adhesion and take the average value of the corrosion area on the surface of the corrosion-resistant high-performance steel structure under the same solution in the same embodiment;

[0173] As shown in the following table:

[0174] Table 1 (Corroded Area)

[0175]

[0176] Table 2 (Wall hanging condition)

[0177] project Solution wall adhesion Example 1 Small amount Example 2 Very small amount Example 3 Small amount Comparative Example 1 Small amount Comparative Example 2 Small amount

[0178] It can be seen from the above table that the corrosion-resistant high-performance steel structure prepared in Example 2 is the best compared with Example 1, Example 3 and Comparative Examples 1-2. The corrosion-resistant agent prepared by the modified agent, chromium, nickel, manganese and aluminum effectively improves the smoothness of the surface of the corrosion-resistant high-performance steel structure, minimizes the wall hanging ability of the corrosive solution, and reduces the contact time between the corrosive solution and the surface of the corrosion-resistant high-performance steel structure, thereby improving the corrosion resistance of the corrosion-resistant high-performance steel structure.

[0179] 3.2 Crack resistance and fire resistance test

[0180] 1) Experimental Materials

[0181] 2) Experimental procedures

[0182] ① Five pieces of corrosion-resistant high-performance steel structures prepared in Example 2 and Comparative Examples 3-6, each piece is 2m long*2m wide*1cm thick;

[0183] ② Place the steel sample under the flame generator to ensure that the flame can evenly irradiate the sample surface. At the same time, use a thermal radiation meter and a thermometer to monitor and record the temperature data. After 1 hour of flame, cool naturally;

[0184] ③ Taking the average value of the crack length, crack depth, crack width and crack number on the corrosion-resistant high-performance steel structure prepared in the same embodiment or comparative example;

[0185] As shown in the following table:

[0186] Table 3 (crack length, crack depth, crack width, number of cracks)

[0187] project Crack length (cm) Crack depth (cm) Crack width (cm) Number of cracks (cm) Example 2 1.1 0.01 0.0001 3 Comparative Example 3 3.3 0.07 0.01 7 Comparative Example 4 3.7 0.06 0.0111 6 Comparative Example 5 4.1 0.06 0.0141 7 Comparative Example 6 2.6 0.063 0.1324 11

[0188] It can be seen from the above table that compared with comparative examples 3-6, the corrosion-resistant high-performance steel structure prepared in Example 2 is the best, and the anti-cracking refractory agent prepared by short mullite fiber, coal gangue powder and short zirconia refractory fiber effectively reduces the crack length, crack depth, crack width and number of cracks, thereby improving the anti-cracking and refractory ability of the corrosion-resistant high-performance steel structure.

[0189] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A corrosion-resistant high-performance steel structural material, characterized in that: The raw materials for its preparation include, by weight: 1-3 parts of carbon, 64-77 parts of iron, 3-6 parts of corrosion resistant agent, and 2-5 parts of anti-cracking fireproof agent; Wherein, by weight, the corrosion resistance agent includes 0.4-1.2 parts of impurity modifier, 1-1.3 parts of chromium, 1.2-1.7 parts of nickel, 0.3-0.8 parts of manganese, and 2-4 parts of aluminum.

2. The corrosion-resistant high-performance steel structural material according to claim 1, characterized in that: The preparation process of the modified agent is as follows: (i) Mixing rare earth cerium powder, rare earth praseodymium powder and rare earth scandium powder, controlling the time to be 20-30 minutes, controlling the rotation speed to be 10-13r / min, and obtaining a mixed powder; (ii) Pour the mixed powder into a melting furnace for melting, controlling the temperature to be 2200-2300°C, and controlling the time to be 30-50 minutes, and obtaining a mixed liquid; (iii) Cooling the mixed liquid into a mold to obtain a rare earth block; (iv) Grinding the rare earth block into powder, controlling the powder particle diameter to be 0.001-0.003um, and obtaining rare earth mixed microparticles.

3. The corrosion-resistant high-performance steel structural material according to claim 2, characterized in that: The mass ratio of the rare earth cerium powder, the rare earth praseodymium powder and the rare earth scandium powder is 1:0.2:0.

4.

4. The corrosion-resistant high-performance steel structural material according to claim 1, characterized in that: The preparation process of the anti-cracking fireproof agent is: (i) Mix short mullite fiber, coal gangue powder and short zirconia refractory fiber, control the time to be 20-30min, control the rotation speed to be 10-13r / min, and obtain a mixture; (ii) Spread the mixture on a filter screen, and then spray it with a vulcanizing agent, control the spraying time to be 4-6h, and obtain a vulcanized material; (iii) Rinse the vulcanized material with water, control the rinsing time to be 2-4h, and then dry it to obtain a crack-resistant refractory agent.

5. The corrosion-resistant high-performance steel structural material according to claim 4, characterized in that: The preparation process of the short mullite fiber is as follows: using a fiber crusher to prepare the mullite fiber into short mullite fibers with a length of 1-2 mm and a diameter of 0.1-0.2 um; The preparation process of the short zirconia refractory fiber is as follows: using a fiber crusher to prepare the zirconia refractory fiber into short zirconia refractory fiber with a length of 1-2 mm and a diameter of 0.1-0.2 um.

6. The corrosion-resistant high-performance steel structural material according to claim 4, characterized in that: The mass ratio of the short mullite fiber, the coal gangue powder and the short zirconia refractory fiber is 1:1.2:1.

3.

7. A method for preparing the corrosion-resistant high-performance steel structural material according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1, corrosion resistant agent: mix and stir the impurity modifying agent, chromium, nickel, manganese and aluminum, control the stirring time to 20-30min, and control the stirring speed to 10-13r / min; S2, adding carbon, iron, corrosion resistant agent and anti-cracking refractory agent into an electric arc furnace to obtain molten steel; S3, casting molten steel to form an electrode rod, and isothermally annealing the electrode rod to obtain an ingot; S4, electroslag remelting the ingot to obtain an electroslag ingot; S5, forging the electroslag ingot using a forging machine, and controlling the forging time to be 10-20 minutes; S6, quenching and heat-insulating the electroslag ingot in S5, tempering, and controlling the heat treatment temperature to be 1170°C-1200°C for quenching and 545°C-555°C for tempering; S7. Cryogenically treat the electroslag ingot in S6, control the cryogenic temperature to -163-190°C, and keep it warm for 36-43 hours to obtain a corrosion-resistant high-performance steel structure.